2001
DOI: 10.1111/0017-4815.00165
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Travel Behavior of the Suburban Elderly

Abstract: In recent years, a significant feature of population change in North American metropolitan areas has been the rapid suburbanization of elderly people. The ability to engage in routine activity may be a necessary condition for the maintenance of independent life styles and psychological well-being among older suburbanites. Using a conceptual framework based on Parmelee and Lawton's ecological model of aging, this article offers an exploratory investigation of the determinants of the travel of separate samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 10 publications
0
26
0
4
Order By: Relevance
“…Two other studies have reported older adults' frequency of travel to destinations (King et al, 2003;Smith, 2001) historically, over longer time periods. Smith and Sylvestre asked older adult participants to recall the frequency with which they made trips to a pre-determined list of eight destinations in the past year (banks; grocery stores; friends'/relatives' homes; pharmacies; rec centres; place of worship; volunteering/ work; senior centres) (Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies have reported older adults' frequency of travel to destinations (King et al, 2003;Smith, 2001) historically, over longer time periods. Smith and Sylvestre asked older adult participants to recall the frequency with which they made trips to a pre-determined list of eight destinations in the past year (banks; grocery stores; friends'/relatives' homes; pharmacies; rec centres; place of worship; volunteering/ work; senior centres) (Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies have reported older adults' frequency of travel to destinations (King et al, 2003;Smith, 2001) historically, over longer time periods. Smith and Sylvestre asked older adult participants to recall the frequency with which they made trips to a pre-determined list of eight destinations in the past year (banks; grocery stores; friends'/relatives' homes; pharmacies; rec centres; place of worship; volunteering/ work; senior centres) (Smith, 2001). More than 90% of participants reported visiting a grocery store at least once per week; frequency of travel to the other destinations varied based on participants' person-level characteristics (sex, comorbidities, living arrangements, income) (Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participation in social and productive activities contributes to older people's health, cognitive functioning, and well-being (Engelhardt, Buber, Skirbekk, & Prskawetz, 2010;Menec, 2003;Scheiner, 2004;Siegrist & Wahrendorf, 2009), while health restrictions reduce older people's activity frequency (e.g., Scheiner, 2006;Smith & Sylvestre, 2001) and increased their unfulfilled activity wishes Hjorthol, 2013;Scheiner, 2006). The subjective health status and feelings of control (mastery, selfefficacy) appear to be more relevant for the fulfilment of activity wishes than the "objective" health state, measured for example by specific physical symptoms Mandl et al, 2013).…”
Section: Healthmentioning
confidence: 99%
“…The growing demands for mobility and accessibility of this age group grow in significance relative to the needs of younger, nonretired populations (Smith and Sylvestre, 2001;Su and Bell, 2006). Recent findings by P a aez et al (2006) support the proposition that trip-making propensity decreases with age; however, they also find that this behavior is not spatially homogeneous and exhibits a large degree of variability-a finding that highlights the challenges of planning transportation for the elderly.…”
Section: Introductionmentioning
confidence: 99%